2004
DOI: 10.1108/02656710410511678
|View full text |Cite
|
Sign up to set email alerts
|

Reliability‐based analysis of service recovery

Abstract: To succeed, service businesses must offer their customers high-quality, reliable service. However, many of the characteristics that make services unique also make it difficult to ensure consistently correct performance. To promptly identify and correct errors when they occur, service managers have been advised to include recovery steps in their service processes. However, while service recovery has anecdotal support, the literature has so far not offered management tools for analytically evaluating a system's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Part of the reason for this is that the sector is typified by its sheer diversity and the extent of its economic coverage (Dotchin and Oakland, 1994a; Haynes, 1990). As a result of the importance of the sector, there is a well‐established literature relating to the management of service organisations and many of their key attributes have been identified by previous research (Clemes, 2000; Haynes, 1990; Rosen and Karwan, 1994; Simons, 2004; Wemmerlov, 1990). It is in the nature of these characteristics that the roots of the sector's potential for crisis can be identified.…”
Section: Crisis In Context – Elements Of the Service Sectormentioning
confidence: 99%
“…Part of the reason for this is that the sector is typified by its sheer diversity and the extent of its economic coverage (Dotchin and Oakland, 1994a; Haynes, 1990). As a result of the importance of the sector, there is a well‐established literature relating to the management of service organisations and many of their key attributes have been identified by previous research (Clemes, 2000; Haynes, 1990; Rosen and Karwan, 1994; Simons, 2004; Wemmerlov, 1990). It is in the nature of these characteristics that the roots of the sector's potential for crisis can be identified.…”
Section: Crisis In Context – Elements Of the Service Sectormentioning
confidence: 99%
“…Simons (2004) [45] questioned the focus of service recovery on dealing with customers who have been the recipient of poor service and suggested that it should focus more on dealing with the mechanisms that generate errors and improve correction capabilities. Learning from failures moves service recovery away from a transactional activity, interested only in recovering and satisfying an individual customer, toward management activity that improves systems and processes to ensure future customers are satisfied and costs are reduced.…”
Section: Thefinancial Aspect Of Service Recoverymentioning
confidence: 98%
“…And more specifically, little literature contains analytical methodologies that can help managers make the trade-off needed to improve service quality [16].…”
Section: Introductionmentioning
confidence: 99%
“…Reliability is the ability to perform the promised service consistently, dependably, and accurately (Simons, 2004). Reliability has often been cited as the most important dimension in assessing the quality of service and is therefore a fundamental requirement for businesses to compete in the marketplace (Cook et al, 2002).…”
Section: Improvement In Reliability Of Servicesmentioning
confidence: 99%